Physical and chemical characteristics of aerosols over Arabian Sea during ARMEX 2002 - 03 - RAO, P. S. P.; PRAVEEN, P. S.; CHATE, D. M.; ALI, K.; SAFAI, P. D.; MOMIN, G. A. (MAUSAM, 2005)
Total Suspended Particulates (TSP) and size segregated aerosols were collected over Arabian Sea during Arabian Sea Monsoon Experiment (ARMEX) campaign in the monsoon season (June- August, 2002) and in the pre-monsoon season (Feb-March, 2003) onboard Ocean Research Vessel, Sagar Kanya. All the aerosol samples were analysed for major water soluble ionic components. The higher (nearly double) TSP levels in monsoon season than those in pre-monsoon season were observed which may be due to high bubble bursting activity on sea surface due to high winds in monsoon. Chemical composition of aerosols revealed that sea salt (NaCl) is the major contributor to the total ionic composition of aerosols during the monsoon season and the anthropogenic ions i.e., SO4 and NO3 are the major contributors during the pre-monsoon seasons. The size distribution of aerosols showed bimodal with a dominant peak in coarse size. 70% of the total aerosols are contributed by coarse aerosols which are originated from sea. The aerosols were found to be in alkaline nature during the monsoon season and acidic during the pre-monsoon season.